Comparative Possibilities : The Challenge of Contemporary History (Historia, 2021)
EnglishThis article explores and deplores a paradox, namely that while India may be the most interesting country in the world, we know so little about its history as an independent nation. The article identifies the obstacles to the writing of contemporary history, but also outlines how they might be overcome. It suggests some important themes for research – among these are the histories of states, the histories of institutions, and the biographies of writers and activists. Finally, the article suggests that since the study of colonialism is meeting with diminishing returns, contemporary history might and perhaps should become a “growth area” for the future.   AfrikaansDie Uitdaging van Kontemporêre GeskiedenisHierdie artikel ondersoek en betreur ŉ paradoks, naamlik dat hoewel Indië die mees interessante land in die wêreld mag wees, ons so bitter min van die geskiedenis daarvan as ŉ onafhanklike nasie weet. Die artikel identifiseer die struikelblokke wat bestaan ten opsigte van die skryf van kontemporêre geskiedenis en dui verder ook aan hoe dit oorkom kan word. Dit stel belangrike temas vir navorsing voor – insluitend die geskiedenis van state, die geskiedenis van instellings, asook die biografieë van skrywers en aktiviste. Ten slotte stel die artikel voor dat aangesien die studie van kolonialisme verminderde opbrengste lewer, eietydse geskiedenis dalk ŉ “groei-area” van die toekoms mag, of selfs moet word.
Keywords: Archives; biography; contemporary history; historical sources; Indian historiography; Indian independence; Indian nationalism; oral history; post-independence history; Argiewe; biografie; historiese bronne; Indiese historiografie; Indiese nasionalisme; Indiese onafhanklikheid; kontemporêre geskiedenis; mondelinge geskiedenis; post-onafhanklikheidsgeskiedenis